The influence of glottal and respiratory factors on aerosol emission during phonation - Allison Hilger; Tehya Stockman; Corey Murphey; Jacqueline McCurdy; Shelly Miller (PLoS ONE, 2025)
Introduction Speech-driven aerosol generation plays a key role in airborne disease transmission, yet the physiological mechanisms remain poorly understood. Beyond vocal-fold vibration, airflow and glottal configuration may be key determinants. We tested how phonation type affects aerosol generation while accounting for ventilatory output estimated from exhaled CO₂. Methods Five healthy female adults (22–43 years) sustained vowels across six phonation types: modal register, glottal fry, falsetto register, forced whisper, loud modal register, and vowels preceded by/h/. Aerosol concentration and size distribution (0.1–20 µm) were measured using an aerodynamic particle sizer (APS). Laryngoscopy, conducted in a separate session, was used to estimate the normalized glottal gap during the open phase of phonation (NGG). Exhaled CO₂ range was recorded concurrently as a control for ventilatory variation across tasks. Results Phonation types that had greater ventilatory output and a larger open-phase glottal gap (e.g., forced whispering, loud modal register) produced the highest aerosol concentrations; types with less ventilatory output and smaller open-phase glottal gap (e.g., glottal fry and modal register) produced the lowest. Submicron particles (0.1–1 µm) dominated across conditions. Forced whispering exhibited a bimodal aerosol distribution, with increased emissions at both the smallest (0.1–1 µm) and largest (10–20 µm) particle sizes. Despite the assumption that vocal fold vibration is necessary for aerosol production, whispering, a voiceless sound production, generated a high concentration of particles, suggesting a primary role for airflow and glottal configuration. Normalized glottal gap was the strongest predictor of aerosol output, and CO₂ range (ventilatory output) was also positively associated. Conclusion Sustained sound production can generate substantial aerosols even without vocal fold vibration. The strong association between normalized glottal gap and aerosol output indicates that airflow and glottal configuration, rather than vibration alone, are primary contributors under these task conditions.